Efektivitas Rencana Strategis Pengembangan Pangan Pokok Berbasis Sumber Daya Lokal di Provinsi Lampung - Henita Astuti; Alvi Yani; Suraya Kaffi (Balitbangda Provinsi Lampung, 2018)
Lampung province is being prepared by the government to become a food industry development center with superior products of Beras Siger made from raw cassava which is a food crop commodity. In order to improve the quality and quantity of Rice Siger, the Provincial Government of Lampung delivers through the Local Food Development Program (MP3L) program and increased production of sustainable Beras Siger. This research program was conducted to find out the problems related to, including the ways of cassava during harvest, the type of cassava that can be processed into Siger Rice, the quality of Siger Rice food products, production process procedures, human resources education workers support, available production house sufficient, capable resources, regulation, distribution, distribution of P-IRT permits, and program implementation have been well targeted. The desired results can be used as a consideration, input and information in determining the strategy model and success of the food diversification program of the basics of local resources, alignment of measures to address problems related to various production, demand for input output, agroindustry , government laws and policies to be used that can strengthen the revitalization of food crops for commodities.